A PROPOSED METHOD FOR OBTAINING INTER-WELL TRUE RESISTIVITY (R) FROM SEISMIC DATA – A FIELD TRIAL - Bambang Widarsono; Fakhriyadi Saptono (Scientific Contributions Oil and Gas, 2003)
Information about spatial distribution of rock true resistivity (Rt) throughout an oil or gas field is always desired.